STUDY ON WASTE wATERS OF METAL FINISHING INDUSTRIES AROUND LAHORE METROPOLITAN AREA (Biological Sciences - PJSIR, 2002)
Study was undertaken on the wastewater samples from metal finishing industries of Lahore metropolitan area for  the evaluation of metallic impurities. The metal finishing industry was classified into three categories i.e. medium scale, small scale and cottage scale industry. About 93 wastewater samples were collected  from  various  metal  finishing  industries around Lahore metropolitan  area. In addition to toxic elements  like cadmium, nickel  and zinc the other parameters  such    ashydrogen  ion  concentration  (pH),  Electrical  Conductivity  (EC)  and  Total  Dissolved  Salts (TDS)  were  also determined.